Development of science subject-specific pedagogy to support disaster risk reduction in education: its feasibility and influence - Tyas, Rizki Arumning; Pujianto, Pujianto; Suyanta, Suyanta (Edu sains, 2024)
This research is aimed to (1) produce science subject-specific pedagogy based on discovery learning integrated volcanic eruption disaster consisting of syllabus, lesson plan, student worksheet, and handouts according to experts and learning practitioners, and (2) know the effectiveness of the influence of science subject-specific pedagogy based on discovery learning integrated volcanic eruption disaster to improve mastery concept and disaster preparedness in mitigation. This was a research and development (RD). The research and development used a 4-D model which consists of four stages define, design, develop, and disseminate. The data were collected through (1) Tests, using mastery concept questions and disaster preparedness questions, and (2) Non-tests, using product feasibility assessment instruments filled by experts and learning practitioners and disaster preparedness questionnaires. Data analysis was performed by: (1) Analysis of the feasibility and validity of the Science Subject Specific Pedagogy through the validation of experts and learning practitioners categorized according to the classification of product evaluation categories, and (2) Analysis of research results using descriptive statistical analysis of gain score calculation and inferential statistical analysis of ANOVA multivariate test (MANOVA) using the SPSS 22.0 program. The results of this research and development show that: (1) the Feasibility of science subject-specific pedagogy based on discovery learning integrated volcanic eruption disaster that has been developed, according to expert and learning practitioner assessments are in the category of very good, and (2) The influence of science subject-specific pedagogy based on discovery learning integrated with volcanic eruption disasters is effective to improve mastery concept and students' preparedness in disaster mitigation.